Konvensi dan Inovasi Sastra Melayu Hang Tuah (Studi Perbandingan dalam Prosa dan Puisi) - Ummu Fstimah Ria Lestari (Balai Bahasa Sumatera Utara, 2019)
One of Malay's most famous works of literature today is Hikayat Hang Tuah. Based on the researcher's search, until 2013 this literary work has been transformed in folklore, pictorial stories, and poetry. This research is a qualitative research. This study is a comparative analysis of the structure 1) folklore entitled Hang Tuah by Mosthamir Thalib (2003) and 2) Poet Poet Hang Jebat and Love Hang Tuah-Tuh Teja by Taufik Ikram Jamil (2013). Based on comparative analysis that has been done, it can be concluded that in the Hang Tuah prose written Mosthamir Thalib in the form of folklore, there are some parts that only follow the convention HTT Valentijn, but in other parts there are also innovations made by the author. It can be argued that convention and innovation are in Hang Tuah by Mosthamir Thalib as one of the works of modern Malay literature. Furthermore, for two titles of poetry Taufik Ikram Jamil published in Kompas, September 1, 2013, there is no innovation in the creation of this poem. All the narratives featured in these two titles of poetry refer to Hikayat Hang Tuah.